Cavite City People's Paza a waterfront commercial civic complex and fisherfolk livelihood support facility - Teodosio, Carl Jason B. (College of Architecture, University of the Philippines Diliman, 2020)
Cavite City is a sea-locked 4th class component city in Cavite sandwiched by three bays. It is the oldest and first urbanized city in Cavite. It used to be the center of trade and recreation for the Southern Tagalog. Moreover, its sea-locked setting made it an ideal place for the fisheries industry causing in migration in the 70s and 80s. Fast urbanization of the neighboring municipalities as well as its limited land area and lack of entry points caused the city to turn from a vibrant coastal city to a sea-locked bedroom city. Being a bedroom city, there is an inadequate in-city job opportunities causing people to travel outside the city every day, one ingress and egress to and from the city via land causes bottlenecks and traffic, making the city inadequate to be a bedroom city. With this, comes the thesis problem of how can architecture address the livelihood and public realms issues leading to a stagnating livelihood development in Cavite City in order to improve its economic development. Urban Magnet Theory states that cities with positive magnets attracts people and business ventures leading to a progressive economic development. Cavite City is currently a negative magnet. According to the theory, establishing a strong positive identity is crucial in turning a city from being a negative magnet to a positive magnet. In order to reestablish a strong positive identity, there is a need to capitalize on available resources and revamp the city's identity, there is a need to capitalize on available resources and revamp the city's identity. With this, the thesis statement of the study states that establishing an urban magnet integrating the capitalization on the city bay's economic potential approached through capacity development and the revitalization of the public realm approached through place-making theories will improve the city's stagnating economic situation. The project is an integration of community spaces for productivity, and recreation, saleable commercial spaces and a livelihood support facility for the fisherfolk of Cavite City. The project shall serve as a catalyst for positive urban magnetism for the city shall attract more people -- residents and visitors -- and businesses in the city, hence improving the city's stagnating economic situation.